Pertanggungjawaban Korporasi Atas Perbaikan Lingkungan Hidup Terdampak Limbah Pabrik Perspektif Maslahah: Studi Kasus di Desa Sei Langgei, Kecamatan Bandar Masilam, Kabupaten Simalungun - Eva Yunijar Harahap; Cahaya Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the form of corporate accountability for environmental pollution that occurred in Sei Langgei Village, Bandar Masilam District, Simalungun Regency, which was caused by the operational activities of a palm oil mill. The results of this study also examine this accountability from the perspective of maslahah in Islamic law, in order to see the extent to which the concept of maslahah can be used as a basis for resolving environmental problems.This study uses a qualitative approach with field research and an empirical approach. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation. Data sources were obtained from interviews with the Head of Bandar Masilam District, Village Heads, and affected communities.The results of the study indicate that the activities cause pollution to agricultural land and reduce the quality of life of the community. However, corporate accountability is still limited to administrative steps and has not yet touched on comprehensive environmental recovery. From a maslahah perspective, environmental pollution contradicts the principles of protecting life, property, and the preservation of nature (ḥifẓ al-nafs, ḥifẓ al-māl, and ḥifẓ al-bi’ah), thus corporations should assume broader responsibilities to create public welfare.